2022
DOI: 10.33448/rsd-v11i2.25325
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of enzymatic production of hydrolases and oxyredutases by Fusarium pseudocircinatum and Corynespora torulosa isolated from caesarweed (Urena lobata L., 1753)

Abstract: This work evaluates the enzymatic production of hydrolases and oxireductases by endophytic fungi isolated from leaves of the caesarweed (Urena lobata L.), which is a perennial plant that is well adapted to the Amazon floodplains region, being and is widely used in the production of hessian sacks and other products of natural fiber. Fungi strains Fusarium sp. (1290) and Corynespora sp. (1291) were reactivated, and had their DNA extracted and sequenced to obtain molecular identification. For enzymatic production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…However, Beltagy, Abouelwafa, & Barakat (2022), studying α-amylases purified from Aspergillus flavus, observed amylolytic activities at T= 50° C (71.5 U/mL) and pH= 6.0 (65.17 U/mL) Silva Santiago et al (2022) when studying enzymatic activity of CMCases found that F. pseudocicinatum showed peak enzymatic activity of 0.309 U/mL. However, Aguiar (2017) and Almeida (2015) analyzed the amylase activity from filamentous Research, Society and Development, v. 11, n. 10, e136111032583, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i10.32583 6 fungi and they verified that the highest amylolytic activities were of Aspergillus niger (1.09 U/mL) and Aspergillus brasiliensis (3.8 U/mL), respectively.…”
Section: Activity Enzymementioning
confidence: 99%
“…However, Beltagy, Abouelwafa, & Barakat (2022), studying α-amylases purified from Aspergillus flavus, observed amylolytic activities at T= 50° C (71.5 U/mL) and pH= 6.0 (65.17 U/mL) Silva Santiago et al (2022) when studying enzymatic activity of CMCases found that F. pseudocicinatum showed peak enzymatic activity of 0.309 U/mL. However, Aguiar (2017) and Almeida (2015) analyzed the amylase activity from filamentous Research, Society and Development, v. 11, n. 10, e136111032583, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i10.32583 6 fungi and they verified that the highest amylolytic activities were of Aspergillus niger (1.09 U/mL) and Aspergillus brasiliensis (3.8 U/mL), respectively.…”
Section: Activity Enzymementioning
confidence: 99%